Cardiovascular risk in educators of healthcare professionals. Universidad Técnica del Norte, Ibarra, 2021-2022 - Jorge Gabriel Ponce Ruiz; Adriana Edit Miniet Castillo; Jorge Luis Anaya Gonzalez; Alicia Salome Gordillo Alarcón (Revista Habanera de Ciencias Médicas)
Introduction: Cardiovascular diseases are the main cause of death in the world, causing 2 million deaths annually; 80 % of them in low- or middle-income countries.